Ecohydrological interfaces as hot spots of ecosystem processes. Issue 8 (17th August 2017) - Krause, Stefan; Lewandowski, Jörg; Grimm, Nancy B.; Hannah, David M.; Pinay, Gilles; McDonald, Karlie; Martí, Eugènia; Argerich, Alba; Pfister, Laurent; Klaus, Julian; Battin, Tom; Larned, Scott T.; et al.
Abstract: The movement of water, matter, organisms, and energy can be altered substantially at ecohydrological interfaces, the dynamic transition zones that often develop within ecotones or boundaries between adjacent ecosystems. Interdisciplinary research over the last two decades has indicated that ecohydrological interfaces are often "hot spots" of ecological, biogeochemical, and hydrological processes and may provide refuge for biota during extreme events. Ecohydrological interfaces can have significant impact on global hydrological and biogeochemical cycles, biodiversity, pollutant removal, and ecosystem resilience to disturbance. The organizational principles (i.e., the drivers and controls) of spatially and temporally variable processes at ecohydrological interfaces are poorly understood and require the integrated analysis of hydrological, biogeochemical, and ecological processes. Our rudimentary understanding of the interactions between different drivers and controls critically limits our ability to predict complex system responses to change. In this paper, we explore similarities and contrasts in the functioning of diverse freshwater ecohydrological interfaces across spatial and temporal scales. We use this comparison to develop an integrated, interdisciplinary framework, including a roadmap for analyzing ecohydrological processes and their interactions in ecosystems. We argue that, in order to fully account for their nonlinear process dynamics, ecohydrological interfaces need to be conceptualized as unique, spatially and temporally dynamic entities, which represents a step change from their current representation as boundary conditions at investigated ecosystems. Plain Language Summary: The movement of water, matter, organisms, and energy can be altered substantially at ecohydrological interfaces that we introduce here as a new concept to support the quantitative analysis of nonlinear system behavior stimulated by the complex and multifacetted interactions of hydrological, biogeochemical, and ecological processes across system boundaries. Ecohydrological interfaces are defined here as the dynamic transition zones that may develop at ecosystem (or subsystem) boundaries and control the movement and transformation of organisms, water, matter, and energy between adjacent systems. In this paper, we explore similarities and contrasts in the functioning of diverse freshwater ecohydrological interfaces across spatial and temporal scales. We use this comparison to develop an integrated, interdisciplinary framework, including a roadmap for analyzing ecohydrological processes and their interactions in ecosystems. We argue that, in order to fully account for their nonlinear process dynamics, ecohydrological interfaces need to be conceptualized as unique, spatially and temporally dynamic entities, which represents a step change from their current representation as boundary conditions at investigated ecosystems. Key Points: Ecohydrological interfaces are dynamic transition zones, changing in space and in time Ecohydrological interfaces are defined by their specific functioning often supporting process hot spots and hot moments Interface ecohydrological, biogeochemical, and ecological processes often differ from their neighboring ecosystems